Effect of Early Coronary Collateral Circulation in Patients with ST Elevation Myocardial Infarction - Koirala, Parash; Gajurel, Ratna Mani; Poudel, Chandra Mani; Shrestha, Hemant; Thapa, Sanjeev; Khanal, Rajaram; Shakya, Smriti; Thapa, Shovit; Pathak, Surya Raj (Nepalese Heart Journal, 2023)
Background and Aims: Coronary collateral circulation can develop early after STEMI and patients having these coronary collaterals have favorable outcomes. The aim of this study was to evaluate the prognostic impact of coronary collateral circulation in STEMI. Methods: This is an observational prospective study of 106 consecutive STEMI patients undergoing Primary PCI admitted and treated at a tertiary cardiac centre from May 2019 to April 2020. Clinical profile, complications at index admission and atone month follow up were analyzed. Results: Out of 106 consecutive patients, 50(47%) had early coronary collateral supplying the infarct related artery. The baseline characteristics of the patients in the two groups, with collateral and without collateral, were similar. Among patients with collateral circulation, only 5% had very well developed (Rentrop3) collaterals. The presence of collateral was strongly associated with presence of preexisting angina (p=0.007) and delayed presentation to hospital (p= 0.04). Coronary collateral was more common in non-diabetics, non-anterior wall STEMI and those with mutivessel disease. Compared with the patients without collateral supply, those who had collateral had fewer incidence of in-hospital heart failure (p=0.03) and post MI pericarditis (p=0.04). Conclusion: In STEMI, development or recruitment of early collateral supply to the infarct related artery was associated with lower rates of heart failure, post MI pericarditis, cardiogenic shock, hospital stay and in-hospital deaths. At 1 month, patients with collateral supply had fewer angina recurrence, reinfarcton and stent thrombosis.